Comparative Evaluation of Ozonated Water and 0.2% Chlorhexidine with Scaling and Root Planning in Chronic Periodontitis – A Randomized Controlled Trial - Priyanka Aggarwal; Akshay Bhargava; Shweta Bali; Vaishali Rai Sharma; Amit Garg; Neeti Mittal (Journal of Indian Association of Public Health Dentistry)
Objective: The aim of the study was to compare the efficacy of ozonated water and 0.2% chlorhexidine as subgingival irrigant with scaling and root planing (SRP) in chronic periodontitis. Subjects and Methods: Thirty-one patients with at least one site of 4–6 mm periodontal pocket depth (PD), bilaterally (either maxillary or mandibular arch) were randomly divided into two groups (Group 1 [0.2% chlorhexidine + SRP], Group 2 [ozonated water + SRP]). Plaque index (PI), gingival index (GI), modified sulcular bleeding index (mSBI), PD, and clinical attachment level (CAL) were recorded at baseline, 1, and 3 months and bacterial count at baseline and 3 months. Paired and unpaired t-test was used for statistical analysis. Results: Statistically significant reduction in PI, GI, mSBI, probing PD, and CAL was observed in control and test groups at all intervals of the study (P < 0.05). The intergroup comparison showed a more statistically significant reduction in the test group versus the control group in PI, GI, mSBI, PD, and CAL and microbial culture at 3 months from baseline. Conclusion: Significant improvement in clinical and microbiological parameters suggests that subgingival ozonated water irrigation can be an effective adjunct to SRP in chronic periodontitis.